2021
DOI: 10.3389/fmolb.2021.728661
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain Containing Protein 4 (BRD4) Regulates Expression of its Interacting Coactivators in the Innate Response to Respiratory Syncytial Virus

Abstract: Bromodomain-containing protein 4 plays a central role in coordinating the complex epigenetic component of the innate immune response. Previous studies implicated BRD4 as a component of a chromatin-modifying complex that is dynamically recruited to a network of protective cytokines by binding activated transcription factors, polymerases, and histones to trigger their rapid expression via transcriptional elongation. Our previous study extended our understanding of the airway epithelial BRD4 interactome by identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…In addition, BRD4 promotes iron sequestration in ferritin to withhold it from pathogens, likely implicating this protein in nutritional immunity ( Sui et al, 2019 ). Moreover, BRD4 displays direct antiviral properties, including inhibition of HIV Tat antigen, hence viruses must neutralize this protein to thrive ( Wang et al, 2020 ; Alamer et al, 2021 ; Xu X. et al, 2021 ; Table 1 ). Indeed, several viruses, including HIV and SARS-CoV-2 have developed the ability to usurp BRD4, overcoming nutritional immunity ( Chen I. P. et al, 2021 ).…”
Section: The Brd4/mir-29 Compensatory Systemmentioning
confidence: 99%
“…In addition, BRD4 promotes iron sequestration in ferritin to withhold it from pathogens, likely implicating this protein in nutritional immunity ( Sui et al, 2019 ). Moreover, BRD4 displays direct antiviral properties, including inhibition of HIV Tat antigen, hence viruses must neutralize this protein to thrive ( Wang et al, 2020 ; Alamer et al, 2021 ; Xu X. et al, 2021 ; Table 1 ). Indeed, several viruses, including HIV and SARS-CoV-2 have developed the ability to usurp BRD4, overcoming nutritional immunity ( Chen I. P. et al, 2021 ).…”
Section: The Brd4/mir-29 Compensatory Systemmentioning
confidence: 99%
“…The mechanisms behind how selective BRD4 BD inhibitors disrupt epigenetic control are just beginning to be understood. We recently found that inhibition of BRD4 BDs disrupt association of more than 200 transcription factors in the activated complex ( Mann et al, 2021 ), and that BRD4 inhibitors block expression of key components of transcriptional coactivators, chromatin remodeling proteins as well as BRD4 itself ( Xu et al, 2021 ). Consequently, follow-up studies are needed to determine the mechanisms by which ZL0591 disrupts and reverses bleomycin-induced fibrosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BRD4 controls expression of members of its interacting coactivators that bind the BD, including transcription factors, adaptors and chromatin remodeling complexes. Reproduced with permission from ( Xu et al, 2021a ).…”
Section: Brd4 Regulates Growth Factors and Ecm Remodelingmentioning
confidence: 99%
“…To address the question whether BRD4 dependent genes are regulated by changes in chromatin accessibility, we mapped the BRD4-dependent gene regulatory network to 1700 chromatin-accessible sites in the genome determined by Tn5 transposase-cleavage-next generation sequencing (ATAC-Seq) studies ( Xu et al, 2020 ). Genome ontology and pathway enrichment indicated a substantial enrichment of genes controlling ECM biosynthesis and/or modification ( Xu et al, 2021a ). Specifically, we found that RSV produces nucleosome-free regions on TGFB1/JUNB//FN1/MMP9 genes and GFPT2 ( Xu et al, 2020 ) ( Figure 7 ).…”
Section: Brd4 Regulates Growth Factors and Ecm Remodelingmentioning
confidence: 99%